Enhancing Service Quality Through Employee Training and Development: A Literature Review - Nisifa Prila Anisa; Rizqi Angelika Sumardi; Nabilla Kusuma Dewi; Mohamad Zein Saleh (JURNAL RISET MANAJEMEN (JURMA), 2024)
This study aims to analyze the contribution of employee training and development to improving service quality from a company perspective. Service quality is an important factor in retaining customers and creating a competitive advantage. Effective training helps employees develop the technical and interpersonal skills necessary to provide responsive and empathetic service, which are two important dimensions in service quality assessment. The results of the study show that employee training and development have a positive impact on the company. This study concludes that employee training and development is an important strategy that can improve the quality of service and the company's competitiveness in the market.